DETERMINANT FACTORS OF PATIENT SATISFACTION AND TRUST IN PHARMACY STAFF AMONG PERSONS WITH NON-COMMUNICABLE DISEASES: PATIENT CENTERED CARE APPROACH - Siti Rahayu Nurjanah; Prasojo Pribadi; Puspita Septie Dianita (Jurnal Farmasi Sains dan Praktis, 2022)
Patient satisfaction and trust are the main focus in the context of health care. Patient satisfaction is influenced by medication service factors, handling patient complaints and listening to patient needs. Important to develop and test a patient-centered care model as a tool to monitor, measure, analyze, and increase patient satisfaction and trust among people with non-communicable diseases in Public Health Center service setting. This study attempts to ascertain the effect of care on patient satisfaction and trust in pharmacy staff at the Magelang City Public Health Center. Cross-sectional quantitative research is used in this field. 212 people participated as the sample. Non-probability sampling using a purposive sample strategy was used as the sampling technique in this investigation. Structural Equation Modeling-Partial Least Square (SEM-PLS) is used for hypothesis testing. According to the study's findings, patient satisfaction is positively impacted by pharmacy staffs’ participative behavior and interpersonal communication (p< 0.05). Interpersonal communication and pharmacy staff participation do not affect the trust in pharmacy staff (p> 0.05). Patient satisfaction plays a moderating role in the association between pharmacy staff participation and trust in pharmacy staff (p< 0.05). Likewise, the association between interpersonal communication and trust in pharmacy staff is mediated by patient satisfaction (p< 0.05).